Neutron scattering evidence for isolated spin-1/2 ladders in (C5D12N)(2)CuBr4 - Savici, A. T.; Granroth, G. E.; Broholm, C. L.; Pajerowski, D. M.; Brown, C. M.; Talham, D. R.; Meisel, M. W.; Schmidt, Kai Phillip; Uhrig, G. S.; Nagler, S. E. (Physical Review B, 2009)
Inelastic neutron scattering was used to determine the spin Hamiltonian for the singlet ground-state system of fully deuterated BPCB, (C5D12N)(2)CuBr4. A two-leg spin-1/2 ladder model, with J(perpendicular to) = (1.09 +/- 0.01) meV and J(parallel to) = (0.296 +/- 0.005) meV, accurately describes the data. The experimental limit on the effective interladder exchange constant is vertical bar J(int)(eff)vertical bar less than or similar to 0.006 meV, and the limit on total diagonal, intraladder exchange is vertical bar J(F)+J(F')vertical bar <= 0.1 meV. Including the effects of copper to bromide covalent spin transfer on the magnetic form factor, the experimental ratios of intraladder bond energies are consistent with the predictions of continuous unitary transformation.